Technical Instructions for Utilizing Chicken Waste as A Bokashi Organic Fertilizer in Lepo-Lepo Village, Barug a District, Kendari City - Fuji Astuty Auza; Rusli Badaruddin; Hairil Azulyatno Hadini; Natsir Sandiah; Andi Murlina Tasse; Rahim Aka (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Increasing the population of chickens nationally and regionally will increase the waste generated. If the waste is not managed properly, it has the potential to cause environmental pollution, especially from manure that is produced by livestock every day. Livestock rearing produces a lot of waste/manure which is abundant and has not been used properly by the community. Chicken is one of the animals or livestock whose livestock manure contains nutrients and organic matter which is quite high and has the potential to produce organic fertilizer which is needed for the maintenance of soil fertility. Organic fertilizers produced from the fermentation of organic materials such as compost and manure using the help of effective microorganism technology (EM4) are known as bokashi. The purpose of this activity is to provide guidance and counseling in managing and utilizing chicken manure waste as organic bokashi fertilizer as well as providing economic benefits and benefits to farmers/breeders. The activity approach method is carried out by (1) lectures and discussions about the prospects and benefits obtained from chicken manure processing technology, (2) demonstrations in providing in-depth understanding and introduction of ingredients used in the manufacture of organic bokashi fertilizer, (3) the practice of making organic bokashi fertilizer using EM4 technology. The counseling material presented received a positive response and the participants were quite enthusiastic, considering that so far, the manufacture of fertilizers has been carried out without a touch of technology. It was concluded that the practice of making organic bokashi fertilizer in addition to increasing livestock production can also increase the income of farmers from the sale of organic bokashi fertilizer.